2013
DOI: 10.1245/s10434-012-2831-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Margin Status and Reexcision in Local Recurrence Following Breast Conservation Surgery

Abstract: Our reexcision rate is low compared with other reports. This results from a policy that defines "no tumor on ink" as an adequate margin for BCS, and the use of selective irradiation boosts based on margins assessed by our pathologists. Our local recurrence rate compares favorably with those seen in other studies while minimizing the need for additional operations. A higher IBTR rate after reexcision likely reflects tumor biology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 18 publications
2
15
1
Order By: Relevance
“…However, as stated in the recent SSO-ASTRO-Guidelines [47] margins need to be cleared in terms of "no ink on margins". Contrary to our findings in this cohort, there is evidence in other studies that unclear margins affect local recurrence and disease-free survival [48], especially in high-risk tumor subtypes, as we also found most recently in a cohort of 2037 patients with triple-negative breast cancer [49]. Traditional prognostic factors like T-size [50,51] in a cohort with a typical distribution of national mammography screening from 50 to 69 years with predominantly T1 and T2-tumors did not show a significant increase of recurrence rate from T1 to T2 stage.…”
Section: Discussioncontrasting
confidence: 99%
“…However, as stated in the recent SSO-ASTRO-Guidelines [47] margins need to be cleared in terms of "no ink on margins". Contrary to our findings in this cohort, there is evidence in other studies that unclear margins affect local recurrence and disease-free survival [48], especially in high-risk tumor subtypes, as we also found most recently in a cohort of 2037 patients with triple-negative breast cancer [49]. Traditional prognostic factors like T-size [50,51] in a cohort with a typical distribution of national mammography screening from 50 to 69 years with predominantly T1 and T2-tumors did not show a significant increase of recurrence rate from T1 to T2 stage.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, re‐excision was associated with a high risk of IBTR. A similar result was found by Groot et al and Adams et al . A delay in adjuvant therapy has been proposed as a possible explanation because delays have been associated with IBTR , but inadequate re‐excision due to poor orientation of the initial specimen could also be a contributing factor.…”
Section: Discussionsupporting
confidence: 83%
“…Adams et al in concordance with NSABP guidelines, evaluated the role of an institution-wide policy of "no tumor on ink" (See Fig. 1) as a definition of negative margins, and found that this did not lead to an increase in local recurrence in their institution [41]. This is in agreement with several other retrospective cohort studies and opinions from leaders in the field, however these studies are all level 3 evidence [42][43][44].…”
Section: No Tumor On Inksupporting
confidence: 69%